PENYULUHAN PENGENALAN DUNIA DIGITAL MARKETING BAGI DESA CIBODAS - Hendra Bunyamin; Julianti Kasih; Tiur Gantini; Teddy Marcus; Hapnes Toba; Djoni Setiawan; Sherly Santiadi; Rolando Vieri (Politeknik Negeri Sriwijaya, 2022)
The social media revolution has completely changed consumer behavior as well as the Internet. A marketing strategy which reaches consumers through internet usage channels, mobile devices, search engines, and social media in the broadband Internet corridor is needed by businessmen nowadays. This marketing strategy so-called digital marketing is required to compete for customers in the 21st century. Specifically in this community dedication project, we deliver a webinar to educate villagers from Desa Cibodas about digital marketing skills to create business opportunities by utilizing digital platforms. Additionally, this webinar is a part of Digital Village program which is a joint cooperation between Dinas Komunikasi dan Informatika Provinsi Jawa Barat and Asosiasi Pendidikan Tinggi Informatika dan Komputer (APTIKOM). Keywords: community dedication, digital marketing, entrepreneurship